DIFFERENCES IN EFFECTIVENESS OF ANTIHYPERTENSIVE THERAPY IN MEN AND WOMEN: LOSARTAN VERSUS ENALAPRIL - E. I. Tarlovskaya; D. A. Suvorova; A. A. Sobolev (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate gender differences in effectiveness of antihypertensive therapy with losartan in comparison with enalapril therapy. Material and methods. Open-label controlled crossover study in parallel groups was conducted during 3 months. A total of 120 patients aged 20-45 years with arterial hypertension (HT) of 1 and 2 degree were split into 4 groups with 30 patients in each: 1A, 1B – men; 2A, 2B – women. For the first 6 weeks patients of the 1A, 2A groups received enalapril 5-20 mg while patients of 1B, 2B – received losartan 50-100 mg. Then the therapy was crosswise changed. Results. Initial blood pressure (BP) levels did not differ significantly in men and women. In women start therapy with losartan decreased systolic BP (BPs) more effectively than enalapril therapy did (18.2±5.4% vs 15.2±4.3%, р=0.02). In men enalapril and losartan start therapies did not show significant differences in BP reduction (13.8±4.5% vs 14.6±4.6%, р=0.539). Follicule-stimulating hormone (FSH) level in women correlated positively with age (r=0.826; p=0.0001), HT duration (r=0.498; p=0.0001), BPs level (r=0.466; p=0.001), microalbuminuria level (r=0.583; p=0.0001) and negatively – with glomerular filtration rate (r=-0.58; p=0.0001). Conclusion. Losartan is more effective than enalapril as a start therapy in 20-45-year-old women. In women FSH level correlates with age, HT duration, BPs and microalbuminuria levels, glomerular filtration rate.